Analisis Bibliometrik dengan VOSViewer: Tren Material, Fasad, Bangunan dan Kenyamanan Termal dalam Arsitektur Berkelanjutan - Ayu Hidayani; Almira Nindya Nareswari; Muhammad Hasan; Ratih Widiastuti (Universitas Muhammadiyah Palembang, 2025)
Research on sustainability has been increasing eah year with the emergence of global trends and movement towards more environmentally friendly lifestyle. This study employs bibliometric analysis methods to produce graphical and visual analyses related to research trends in sustainable architecture. Data were collected through a search in Scopus, resulting in the identification of 101 documents published between 2015 - 2025 based on specific criteria. The on-site Scopus analysis system was used for graphical analysis, and VOSViewer was utillized for visualizing research trends. The analisis revealed five significant research groups: sustainable design, thermal comfort, thermal performance, enviromental quality, and sustainable construction. From the analysis, it can be concluded that there is significant potential for further research on topics related to thermal comfort and sustainable architecture. Therefore, this study is expected serve as a valuable reference for further research.